Towards a Working Definition of Negotiation in Telecollaboration: Analysis of Teletandem Oral Sessions - Aranha, Solange; Rampazzo, Laura (Colombian Applied Linguistics Journal, 2022)
As digital techonology advances, geographically distant learners have been engaging in cross-cultural communication and negotiation via telecollaborative projects. Research has shown that negotiation of meaning is crucial for effective communication in these scenarios, nonetheless, more studies are needed to investigate other types of negotiation, given its importance for establishing cooperation. This paper aims at exploring the negotiation patterns between dyads in 10 sessions selected from Multimodal Teletandem Corpus and provides a working definition of negotiation in telecollaboration. Participants, who were university students in Brazil and abroad and were enrolled in language classes, met online to help with practicing each other’s language and were expected to exchange information about themselves in the first synchronous session. Through a qualitative analysis of the transcripts of the 10 sessions, we identified moments in which the conversation was suspended to negotiate meaning, technology issues, separation of languages, and aspects related to the tasks requested by their professors. Our analysis shows that negotiation in telecollaboration may be motivated by aspects internal to the conversation, such as meaning, or by external factors, as with problems with equipments, tasks, or with deciding the language to speak. Findings suggest that negotiation serves an essential purpose as it allows participants to make collaborative decisions and resolve conflicts that, otherwise, could prevent conversation to continue. Results may prove useful for researchers and practicioners interested in telecollaboration, who design and guide participants through learning in such contexts.